A multiproxy reconstruction of the palaeoenvironment and palaeoclimate of the Late Pleistocene in northeastern Iberia: Cova dels Xaragalls, Vimbodí-Poblet, Paratge Natural de Poblet, Catalonia - López-García, Juan Manuel; Blain, Hugues-Alexandre; Bennàsar, Maria; Euba, Itxaso; Bañuls, Sandra; Bischoff, James; López-Ortega, Esther; Saladié, Palmira; Uzquiano, Paloma; Vallverdú, Josep (Boreas, 2012)
The Cova dels Xaragalls is a small open karst system, located in the municipality of Vimbodí-Poblet (Tarragona, Catalonia, NE Spain). It is an important Holocene archaeological site that was inspected in the 1970s but from which little has been published. New excavations starting in 2008 have exposed a deep Late Pleistocene stratigraphical sequence. In this paper, we present for the first time palaeoenvironmental and palaeoclimatic reconstructions of this Late Pleistocene succession on the basis of both the small-vertebrate assemblages and the charcoals. Results from the small-vertebrate associations along the sequence indicate that the landscape had open-woodland habitats in the vicinity of the Cova del Xaragalls, with wet points in the surrounding area. Woodland habitats were dominant throughout the sequence, as evidenced by the abundance of the species Apodemus sylvaticus, but were better developed during warm periods (layers C5 and C8), whereas during cold periods (layers C4 and C3) the environment was slightly more humid in response to higher mean annual precipitation and the opening of the landscape. The charcoal analysis indicates that the woodland surrounding the cave was composed mainly of Pinus (more than 90% was identified as Pinus), but that during the cold period (C3–C4) it incorporated some Quercus ilex/coccifera and Angiosperm indet., probably linked with greater precipitation. Comparisons are made with other long palaeoenvironmental sequences from the northeastern Iberian Peninsula and with global marine isotopic curves, providing a scenario for the palaeoclimatic and palaeoenvironmental changes that occurred during the Late Pleistocene in the woodland areas surrounding the Cova dels Xaragalls.
Keywords: CHARCOAL ANALYSIS; Cova dels Xaragalls; Late Pleistocene; Open woodlands (voyant); palaeoclimatic changes; palaeoenvironmental changes; small-vertebrate assemblages